(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
Studies on trypophobia (or fear of holes) are scarce to date, and is more often discussed in informal texts, websites, and social networks. The purpose of this article is to present the case of a young woman who complained about experiencing strong physiological responses such as nausea and rapid heartbeat when in the presence of stimuli comprising clusters of holes. These situations are usually related to organic surfaces such as human skin. Some characteristics of her phobic avoidance’s behaviors are covering with her hands an image containing holes to avoid it or requesting another person to stop reporting a story that triggers these aversive stimuli. The treatment applied, based on behavioral approach, is comprised of an initial assessment phase, carried out through interviews and self-monitoring; a treatment phase based on psychoeducation, respiratory training, stimulus hierarchy, systematic desensitization, and a follow-up phase. The results demonstrate the effectiveness of intervention strategies to decrease the physiological responses and to increase alternative behaviors as coping behaviors.